Les manuscrits arabo-africains : des particularités ? - Constant Hamès (Revue des Mondes Musulmans et de la Méditerranée)
Having been marginalized for a long period of time both by classical Orientalism as well as by the historical and ethnological sciences, written Arab-African literature, which is extremely prolific, is just beginning to be discovered. Questions about its constitution (where, when, how, by whom), the material upon which it was written (what kind of paper was available in Africa), its linguistic characteristics (languages, kinds of writing), material conditions (manufacture, preservation), inventories and catalogues - despite recent breakthroughs - is just beginning to come up.